Standardisation of gum-oleoresin extraction technique in matti (ailanthus triphysa (dennst.) alston.) - Dipti Choudhury (Department of Forest Management and Utilisation, College of Forestry, 2018)
The research work entitled "Standardisation of gum-oleoresin extraction technique in Matti (Ailanthus triphysa (Dennst.) Alston.)" was carried out April 2017 to April 2018. The experiment was carried out in the field of Instructional Farm, College of Horticulture, KAU, Vellanikkara. The main objective was to develop an appropriate technique for extraction of gum-oleoresin and also to study the correlation between tree dimension and anatomical features with gumoleoresin production in Ailanthus triphysa. A total of twenty-seven trees were selected for conducting the study in which three girth classes (<75, 75-150, >150) and three extraction technique each with three replication were taken. Data analysis done for monthly interval, showed significant difference in girth class except in the month of July and August and for extraction technique it was found to be non-significant difference for all the months except May. Data analysed for different seasons revealed that the girth class <75 was found to be significantly different from other girth classes i.e., 75-150 and >150. Different extraction techniques were found to be non-significant for all the three seasons. Effect of season and treatment (girth x extraction techniques) on gumoleoresin yield was found to be significantly different. The highest quantity of gum oleoresin was reported in post-monsoon season (65.15 g/tree/season) followed by monsoon (39.23 g/tree/season) and least in summer season (18.08 g/tree). Analysis for whole study period revealed that girth class <75 was found to be significantly different from girth classes >75. As the amount of gum-oleoresin yield was obtained from girth class >150 cm (712.07 g/year) and in 75-150 cm girth class, (604.06 g/year) and least in girth class <75cm (147.64 g/year). It was found to be non-significant for different extraction techniques. 128 Anatomical study unveiled the deposition of gum-oleoresin in vessels through the pits present on the walls of vessels and it was also observed that the ray parenchyma was playing an important role in production of gum-oleoresin as the rays are mainly meant for radial conduction. The effect of bark thickness and girth on production of gum-oleoresin was found to be significant with correlation coefficient 0.65 and 0.82 respectively. The climatic parameters like temperature, relative humidity, Rainfall, number of rainy days, sunshine hours, wind speed was found to be nonsignificantly related with gum-oleoresin production. The present study carried out during April 2017 to April 2018, concluded that the trees having <75 girth should not be tapped as its yield was found to be very low. For the extraction of gum oleoresin, all the three methods can be used as it has no effect on the gum-oleoresin production. The present study also revealed that the gum-oleoresin production was less during the summer season. So, the tapping can be avoided during that period.